تقریری احادیث کی روشنی میں ایمان اور تبرک سے متعلق معاصر مسائل کا شرعی استنباط: (ایک تحقیقی جائزہ): Shariah Interpretation of Contemporary Issues Related to Faith and Sanctification in The Light of Taqriri Hadith: (A Research View) - Abdul Qadeer Siddiq,; Dr Shahid Amin, (Al Manhal Research Journal, 2025)
The biography of the Prophet Muhammad (peace be upon him) is not just a treasure of the past, but a practical example for every era of humanity. The sayings, actions, and silent approvals of the Prophet (peace be upon him) are a proof for the Ummah. While verbal and practical hadiths are more well-known, the "Sunnah Taqreeriyah" (silent approval hadiths) hold great importance in jurisprudential deduction. This Sunnah Taqreeriyah teaches us that sometimes silence is a clear message. When the Prophet (peace be upon him) did not object to a saying or action, it is considered an approval of that act. The silent approvals of the Prophet (peace be upon him) carry deep messages that guide us even centuries later. This is the silent influence of the Sunnah Taqreeriyah that can be a guiding light in the midst of modern challenges. Now, it is necessary to listen to, understand, and take practical guidance from these silent hadiths. This research article analyzes some important contemporary issues related to faith and blessings (Tabarruk) in the light of these silent approvals, including: Faith in the attributes of Allah- Strong faith and conviction in Allah and the Prophet- The Prophetic method of interfaith dialogue- The issue of Tabarruk (seeking blessings)- The ruling on seeking blessings from the relics of Prophets and non-Prophets- Avoiding personality cult and extremism- The participation of women in Gender Studies and Islamic knowledge- Ethical principles for the perfume industry and medicine.